The best possible self‐intervention as a viable public health tool for the prevention of type 2 diabetes: A reflexive thematic analysis of public experience and engagement. (13th July 2021) - Gibson, Benjamin; Umeh, Kanayo; Davies, Ian; Newson, Lisa
Abstract: Background: Public health initiatives seek to modify lifestyle behaviours associated with risk (e.g., diet, exercise, and smoking), but underpinning psychological and affective processes must also be considered to maximize success. Objective: This study aimed to qualitatively assess how participants engaged with and utilized the best possible self (BPS)‐intervention specifically as a type 2 diabetes (T2D) prevention tool. Design and Methods: Fourteen participants engaged with a tailored BPS intervention. Reflexive thematic analysis analysed accounts of participant's experiences and feasibility of use. Results: All participants submitted evidence of engagement with the intervention. The analysis considered two main themes: Holistic Health and Control. The analysis highlighted several nuanced ways in which individuals conceptualized their health, set goals, and received affective benefits, offering insights into how people personalized a simple intervention to meet their health needs. Conclusions: To our knowledge, this is the first study to tailor the BPS intervention as a public health application for the prevention of T2D. The intervention enabled users to identify their best possible selves in a way that encouraged T2D preventive behaviours. We propose that our tailored BPS intervention could be a flexible and brief tool to assist public health efforts in encouraging change to aid T2D prevention. Public Contribution: The format, language and application of the BPS intervention were adapted in response to a public consultation group that developed a version specifically for application in this study.